ANALISIS PENGGUNAAN MEDIA LOOSEPART DALAM UPAYA MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS PADA ANAK USIA 5-6 TAHUN DI TK KRISTEN GMIT KOINONIA KUPANG - Wujo, Febronia; Kristin Margiani; Angelikus Nama Koten; Yohana Yuniati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was conducted to analyze the use of looseparts media in developing the critical thinking skills of children aged 5–6 years at GMIT Koinonia Christian Kindergarten, Kupang. The study was motivated by the fact that classroom learning remained predominantly teacher-centered, limiting children's opportunities to explore, express ideas, solve problems, and develop critical thinking independently. The objective of this research was to describe the implementation of loosepart media, identify the supporting and inhibiting factors, and examine the teacher’s role in facilitating learning activities that foster critical thinking. This study employed a qualitative descriptive approach. The research subjects consisted of the principal, classroom teachers, and children. Data were collected through observations, semi-structured interviews, and documentation. Data validity was ensured through source and technique triangulation, while data were analyzed using the Miles and Huberman model, including data collection, data reduction, data display, and conclusion drawing. The findings revealed that the use of loosepart media provided children with opportunities to explore, classify objects, arrange patterns, compare, solve simple problems, and make decisions, thereby stimulating their critical thinking skills. The successful implementation was supported by teacher creativity, the availability of learning materials, and children's enthusiasm. However, challenges remained, including limited variation of loosepart materials and teachers' tendency to provide excessive guidance during learning activities. Therefore, loosepart media can serve as an effective child-centered learning alternative to promote critical thinking skills in early childhood.